Death from Diamox: Three Case Reports - M Abdul Moqeet Khan, Tayyab Afghani, Sultan Asif Kiani (Pakistan Journal of Ophthalmology, 2007)
Diamox –Acetazolamide is an inhibitor of enzyme carbonic anhydrase and a nonbacteriostatic sulfonamide. It is widely used in ophthalmic practice to prevent and control abnormal rise in intra-ocular pressure in glaucoma, pre-operative prophylaxis in intra-ocular surgery, prophylaxis after YAG laser, cystoid macular edema and retinal arterial occlusion etc. It is also used in nonophthalmic practice like acute mountain sickness1, peptic ulcer2, idiopathic intracranial hypertension in pregnancy3, chronic hydrocephalus4, epilepsy5, obstructive sleep apnea6 etc.